Differential Signature of the Centrosomal MARK4 Isoforms in Glioma. (2011) - Magnani, Ivana; Novielli, Chiara; Fontana, Laura; Tabano, Silvia; Rovina, Davide; Moroni, Ramona F.; Bauer, Dario; Mazzoleni, Stefania; Colombo, Elisa A.; Tedeschi, Gabriella; Monti, Laura; Porta, Giovanni; et al.
Abstract : Background: MAP/microtubule affinity-regulating kinase 4 (MARK4) is a serine-threonine kinase expressed in two spliced isoforms, MARK4L and MARK4S, of which MARK4L is a candidate for a role in neoplastic transformation. Methods: We performed mutation analysis to identify sequence alterations possibly affecting MARK4 expression. We then investigated the MARK4L and MARK4S expression profile in 21 glioma cell lines and 36 tissues of different malignancy grades, glioblastoma-derived cancer stem cells (GBM CSCs) and mouse neural stem cells (NSCs) by real-time PCR, immunoblotting and immunohistochemistry. We also analyzed the sub-cellular localisation of MARK4 isoforms in glioma and normal cell lines by immunofluorescence. Results: Mutation analysis rules out sequence variations as the cause of the altered MARK4 expression in glioma. Expression profiling confirms that MARK4L is the predominant isoform, whereas MARK4S levels are significantly decreased in comparison and show an inverse correlation with tumour grade. A high MARK4L/MARK4S ratio also characterizes undifferentiated cells, such as GBM CSCs and NSCs. Accordingly, only MARK4L is expressed in brain neurogenic regions. Moreover, while both MARK4 isoforms are localised to the centrosome and midbody in glioma and normal cells, the L isoform exhibits an additional nucleolar localisation in tumour cells. Conclusions: The observed switch towards MARK4L suggests that the balance between the MARK4 isoforms is carefully guarded during neural differentiation but may be subverted in gliomagenesis. Moreover, the MARK4L nucleolar localisation in tumour cells features this MARK4 isoform as a nucleolus-associated tumour marker.